Patellar tendon rupture after radial pressure wave therapy – also known as radial shock wave therapy – for patellar tendinopathy: Report of two Cases: Rotura del tendón rotuliano como resultado de la terapia con ondas de choque radiales, para la tendinopatía rotuliana: Reporte de dos casos - Insuasti Abarca, Walter (2021)
Patellar tendinopathy is characterized by anterior knee pain located at the lower pole of the patella at the junction of the patellar tendon. This is often a disabling condition that limits patients' quality of life, affects their ability to participate in sports, and even hinders their normal daily activities. Extracorporeal shock wave therapy (ESWT) has been recognized as a promising and safe alternative for the treatment of various musculoskeletal disorders – including chronic patellar tendinopathy. However, there is limited evidence regarding its side effects, in particular ESWT-associated tendon injuries. To the authors' knowledge, this is the first report demonstrating clinical and radiological evidence of two patients without known risk factors for partial patellar tendon tears that developed this condition after the application of radial pressure wave therapy - also known as radial shock wave therapy - for patellar tendinopathy. ESWT must be applied by properly trained professionals so that specific requirements needed to guarantee an appropriate application technique, minimize possible adverse effects, and improve patient safety could be met.